The Determinants of House Price in Nanning - Pan, Zhongchen (2012)
With the rapid expansion of real estate industry in China, the house price has become a focus of attention for Chinese people. Hedonic model is a popular method in the research of real estate valuation and house market. This model has been applied in China started from 2002, which is gradually maturing. This study mainly use hedonic model to analyse the relationship between house price and its determinants in Nanning market. It will also establish the hedonic price model of Nanning housing market and validate the applicability of this model. Data employed in this study is from a reputable real estate agent named Guangxi Golden Land Real Estate assessment and advisory Ltd. The results show that the most important characteristics for housing market in Nanning includes position house, administration partition of house, design of house, bus lines around, education quality around, natural landscape around and distance to ASEAN conference and exhibition center. All of these factors attributes have positive influences on house price in Nanning.